An Optimized Encryption Algorithm of Fruit And Vegetable Product Traceability Code Based on Embedded System. Issue 1 (January 2021) - Mu, Shile; Wang, Jiamin; Qi, Yue; Tian, Jianying
Abstract: The quality and safety of fruits, vegetables, and other agricultural products is the lifeline of agricultural development. In recent years, the state departments concerned have strengthened the whole process block on the quality of fruits and vegetables, continuously optimized the measures, and continuously improved the quality control level of fruits and vegetable products. Traceability code is the key technology to realize the whole process block and traceability of the whole industry chain. There is a risk that the traceability code will be modified privately in the application process. Once the traceability code is cracked and modified, its important role in the traceability system will be destroyed. In order to prevent the traceability code from being arbitrarily modified, this paper designs and studies an optimization algorithm of traceability encryption based on an embedded system